Pediatric hearing aid fitting - Quar,Tian Kar (Penerbit Universiti Kebangsaan Malaysia, 2021)
The aim of this book is to provide recommendations and guidelines for fitting children with hearing aids. Focus is given on five major components in pediatric hearing aid fitting which include amplification candidacy assessment, selection of hearing aid features, fitting and verification of hearing aids, outcomes assessment, hearing aid orientation and follow-up managements.